How have changes in accessibility and public funding influenced contraceptive use among Norwegian adolescents? A cohort study - Sunniva Sæbø; Finn Egil Skjeldestad (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The Norwegian Government introduced in 2002 a reimbursement scheme for hormonal contraceptives to adolescents at the same time as public health nurses and midwives received authorization to prescribe hormonal contraceptives. This study examines the impact of increased accessibility and public funding on hormonal contraceptive use among adolescents. Material and Methods The Norwegian Prescription Database, Statistics Norway, and Norwegian Institute of Public Health served as data sources for this cohort study. The study population comprised 174 653 Norwegian women born 1989–1990, 1994–1995, and 1999–2000. We examined use of hormonal contraceptives through dispensed prescriptions from age 12 through age 19 with duration of first continuous use as primary outcome. The statistical analyses were done in SPSS using chi‐squared test, survival analysis, and Joinpoint regression analysis with p‐values < 0.05. Results By age 19, ~75% of the cohorts had used at least one hormonal method. The main providers of the first prescription were general practitioners and public health nurses. Starters of progestogen‐only pills (POPs) have increased across the cohorts, while starters of combined oral contraceptives (COCs) have decreased. The use of long‐acting reversible contraceptives (LARCs) has increased since its inclusion in the reimbursement scheme (2015). Most switchers shifted from COCs or POPs as a start method to implants after LARCs became part of the reimbursement scheme. There has been a significant increase across the cohorts in the number of women who continuously used hormonal contraceptives from start to the end of the calendar year they became 19 years with the same method and after switching methods. We could not correlate changes in decreasing trends for teenage births or induced abortions (Joinpoint analysis) to time for implementation or changes in the reimbursement of hormonal contraceptives from 2002. Conclusions Primarily public health nurses and to a lesser extent midwives became soon after they received authorization to prescribe COCs important providers. The expansion of the reimbursement scheme to cover POPs, patches, vaginal ring, and depot medroxyprogesterone acetate in 2006 had minor impact on increasing the proportion of long‐term first‐time users. However, the inclusion of LARCs in 2015 significantly increased the proportion of long‐term first‐time hormonal contraceptive users.